Postoperative nausea and vomiting after general anesthesia for oral and maxillofacial surgery - Apipan, Benjamas (J Dent Anesth Pain Med, 2016)
BACKGROUND: Postoperative nausea and vomiting (PONV) is one of the most common postoperative complications. Despite this, few papers have reported the incidence and independent risk factors associated with PONV in the context of oral and maxillofacial surgery (OMFS). Therefore, we sought to determine the incidence of PONV, as well as to identify risk factors for the condition in patients who had undergone OMFS under general anesthesia. METHODS: A total of 372 patients' charts were reviewed, and the following potential risk factors for PONV were analyzed: age, sex, body mass index, smoking status, history of PONV and/or motion sickness, duration of anesthesia, amount of blood loss, nasogastric tube insertion and retention and postoperative opioid used. Univariate analysis was performed, and variables with a P-value less than 0.1 were entered into a multiple logistic regression analysis, wherein P-values < 0.05 were considered significant. RESULTS: The overall incidence of PONV was 25.26%. In the multiple logistic regression analysis, the following variables were independent predictors of PONV: age < 30 years, history of PONV and/or motion sickness, and anesthesia duration > 4 h. Furthermore, the number of risk factors was proportional to the incidence of PONV. CONCLUSIONS: The incidence of PONV in patients who have undergone OMFS varies from center to center depending on patient characteristics, as well as on anesthetic and surgical practice. Identifying the independent risk factors for PONV will allow physicians to optimize prophylactic, antiemetic regimens.